2012
DOI: 10.4037/ajcc2012773
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Characteristics Associated With Readmission to a Surgical Intensive Care Unit

Abstract: Background Readmission within 48 hours is a leading performance indicator of the quality of care in an intensive care unit. Objective To investigate variables that might be associated with readmission to a surgical intensive care unit. Methods Demographic characteristics, severity-of-illness scores, and survival rates were collected for all patients admitted to a surgical intensive care unit between 1995 and 2000. Long-term survival and quality of life were determined for patients who were readmitted within 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 37 publications
1
8
2
Order By: Relevance
“…Previous studies have indicated that patients with critical health conditions and cumulative organ dysfunctions exhibit an increased risk of readmission. (1,3,4,8-10,32,33) Nonetheless, in the present study, this increased risk was not confirmed by a high SOFA score at ICU discharge.…”
Section: Discussioncontrasting
confidence: 75%
“…Previous studies have indicated that patients with critical health conditions and cumulative organ dysfunctions exhibit an increased risk of readmission. (1,3,4,8-10,32,33) Nonetheless, in the present study, this increased risk was not confirmed by a high SOFA score at ICU discharge.…”
Section: Discussioncontrasting
confidence: 75%
“…Readmitted patients in our study had a lower mean admission APACHE II score (21.2 ± 8.0 vs. 23.2 ± 8.8) and a lower mean TISS-28 score in the first 24 h of their ICU stay (33.7 ± 7.4 vs. 35.2 ±7.8) in comparison to the first-admission patients. Opposite results can be found in the literature, with APACHE II scores found to be higher among readmitted patients in at least two previous studies [27,28]. Our findings were therefore unexpected, and again may stem from the fact that patients discharged from the initial ICU stay constituted only 55%-60% of the initially admitted patients.…”
Section: Discussioncontrasting
confidence: 70%
“…Of the 2923 patients, 95 (3.3%) experienced UIA during their hospital course including 66 bounce backs (69.5%) and 29 unplanned upgrades (30.5%). On average, patients requiring UIA were older (81 [72-88] versus 78 [70-86], P ¼ 0.04) and more severely injured as measured by ISS (10 [5-17] versus 9 [4][5][6][7][8][9][10][11][12][13] , P < 0.01). Of note, only 26.3% of patients who required UIA had an ISS >15.…”
Section: Risk Factors For Uia In Geriatric Trauma Patientsmentioning
confidence: 99%
“…11 Although prior studies have assessed risk factors for ICU readmission in various settings, none have focused specifically on geriatric trauma patients. 4,9,10,12,13 Furthermore, few studies have included patients who required unplanned upgrade to the ICU after initial admission to the floor. Identifying and addressing risk factors for UIA in geriatric trauma patients is critical for improving patient outcomes.…”
Section: Introductionmentioning
confidence: 99%